Treatment of aplastic anemia with testosterone enanthate - Quesada Velásquez, Norberto (1969)
We treated 10 patients with aplastic anemia res, two with hypercellular bone marrow, showing the first peripherally anemia and leukopenia and anemia only second. The remaining eight cases had aplastic bone marrow with peripheral pancytopenia. All patients received testosterone enanthate periods between three and twelve months, with intramuscular administration. Three patients were given 100 mgms. twice weekly. One received 100 mgms. twice a week but he died the first month of treatment. The rest received 250 MQMs. twice weekly. We managed to get a referral in five cases, one died and four were refractory to treatment. Remission was accompanied by normalization of ferrokinética.